1970
DOI: 10.1042/bj1160437
|View full text |Cite
|
Sign up to set email alerts
|

Species differences in the aromatization of quinic acid in vivo and the role of gut bacteria

Abstract: 1. The fate of (-)-quinic acid has been investigated in 22 species of animals including man. 2. In man and three species of Old World monkeys, i.e. rhesus monkey, baboon and green monkey, oral quinic acid was extensively aromatized (20-60%) and excreted in the urine as hippuric acid, which was determined fluorimetrically. 3. In three species of New World monkeys, i.e. squirrel monkey, spider monkey and capuchin, in three species of lemurs, i.e. bushbaby, slow loris and tree shrew, in the dog, cat, ferret, rabb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 11 publications
0
41
0
Order By: Relevance
“…QA was converted into benzoic acid by gut flora in all species (Figure 1-4). 27,73,86 In summary, bioavailability of QA in animal is very low.…”
Section: Bioavailability Of Qamentioning
confidence: 95%
See 4 more Smart Citations
“…QA was converted into benzoic acid by gut flora in all species (Figure 1-4). 27,73,86 In summary, bioavailability of QA in animal is very low.…”
Section: Bioavailability Of Qamentioning
confidence: 95%
“…85 Adamson in 1970 reported that the aromatization of QA was different between animal species, and gut bacteria played an important role in this process. 27 In man and some old world monkeys, oral quinic acid was extensively aromatized (20-60%) and excreted in the urine as hippuric acid. The aromatization of oral quinic acid was considerably suppressed when gut flora were suppressed by neomycin.…”
Section: Bioavailability Of Qamentioning
confidence: 99%
See 3 more Smart Citations